2012
DOI: 10.1242/jcs.038083
|View full text |Cite
|
Sign up to set email alerts
|

Centrosome positioning in vertebrate development

Abstract: SummaryThe centrosome, a major organizer of microtubules, has important functions in regulating cell shape, polarity, cilia formation and intracellular transport as well as the position of cellular structures, including the mitotic spindle. By means of these activities, centrosomes have important roles during animal development by regulating polarized cell behaviors, such as cell migration or neurite outgrowth, as well as mitotic spindle orientation. In recent years, the pace of discovery regarding the structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(110 citation statements)
references
References 169 publications
(164 reference statements)
3
103
2
2
Order By: Relevance
“…Nevertheless, we observe that specification of the anterior-posterior body axis, which requires Wnt, Nodal, BMP, and FGF signaling, is normal in the absence of centrioles and centrosomes. It has been suggested that centrosomes are important in directed cell migration (55), but the polarized collective migration of the anterior visceral endoderm (56) is normal in the absence of centrioles, as shown by the formation of a single anterior-posterior body axis in Sas4 −/− embryos. Similarly, the apical-basal oscillations of nuclei in pseudostratified epithelia (interkinetic nuclear migration) are thought to depend on an apically anchored centrosome (57), but restriction of mitotic cells to the apical surface of the neural epithelium is normal in Sas4 −/− mutants ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we observe that specification of the anterior-posterior body axis, which requires Wnt, Nodal, BMP, and FGF signaling, is normal in the absence of centrioles and centrosomes. It has been suggested that centrosomes are important in directed cell migration (55), but the polarized collective migration of the anterior visceral endoderm (56) is normal in the absence of centrioles, as shown by the formation of a single anterior-posterior body axis in Sas4 −/− embryos. Similarly, the apical-basal oscillations of nuclei in pseudostratified epithelia (interkinetic nuclear migration) are thought to depend on an apically anchored centrosome (57), but restriction of mitotic cells to the apical surface of the neural epithelium is normal in Sas4 −/− mutants ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These studies also raise implications about the potential of centrosome-associated degradation in controlling subcellular organization in other contexts if additional, well-established observations of centrosome positioning are considered. Given that centrosomes have been shown to act as polarity cues in multiple systems 93,94 and tend to assume stereotyped subcellular positions in a number of differentiated cell types (epithelial cells, migrating fibroblasts), 95 it could be imagined that centrosome-associated degradation may be used as a strategy to locally deplete polarity-determining factors from certain subcellular domains in order to contribute to intracellular organization.…”
Section: Local Degradation By Centrosomal Proteasomes Controls Neuronmentioning
confidence: 99%
“…As cholesterol is released from LDL in the acidic environment of late endosomes, cholesterol might act as maturation signal that induces the transport of mature endosomes towards the minus ends of microtubules [which are typically organized by a microtubule-organizing center (MTOC)]. In non-polarized cells, the MTOC is located adjacent to the nucleus in the center of the cell (Tang and Marshall, 2012). Increases in late endosomal cholesterol allow recruitment of the dynein motor and transport towards the MTOC, and therefore the transport of mature endosomes deeper into cells.…”
Section: Er In Control Of Endosomal Maturationmentioning
confidence: 99%